Optimalisasi Peran Pemuda Desa Peron dalam Pengembangan Social Entrepreneurship Berbasis Limbah Kopi - Daffa Evan Pradama; Muhammad Agnaf Naufal; Aurelia Dias Nanda Revalina; Aira Trismadya Primagati; Rizqa Najwa; Farid Nur Hidayat; Amnan Haris (LPPM Institut Teknologi Kalimantan, 2025)
Peron Village is one of the local coffee centers that produces abundant post-harvest waste in the form of coffee grounds and husks. So far, this waste has not been optimally utilized and has the potential to pollute the soil, increase organic pollution, and reduce the quality of the rural environment. This condition calls for innovation based on the circular economy. The hypothesis of this study is that the involvement of young people through a social entrepreneurship approach in coffee waste management can create environmentally friendly innovations while strengthening local economic resilience. This study uses a descriptive qualitative method with in-depth interviews, observation, and documentation techniques, as well as validation through source and method triangulation. Research informants included members of the Karang Taruna youth organization, coffee farmers, community leaders, and micro-business actors in Peron Village. The results showed that young people played an active role in processing coffee waste into liquid organic fertilizer, cascara, and briquettes. These products not only reduce environmental pollution but also increase soil fertility, open up opportunities for functional food businesses, and provide environmentally friendly alternative energy. The involvement of young people demonstrates their strategic role as agents of change who integrate social, economic, and environmental benefits. The conclusion of this study confirms that coffee waste processing based on social entrepreneurship is an effective youth empowerment strategy, supporting the achievement of SDGs 7, 12, and 15, and has the potential to be replicated in other villages to promote sustainable development.